Metabolic Responses to Reductive Stress - Xiao, Wusheng; Loscalzo, Joseph (Antioxidants & redox signaling, 2020)
Reducing equivalents (NAD(P)H and glutathione [GSH]) are essential for maintaining cellular redox homeostasis and for modulating cellular metabolism. Reductive stress induced by excessive levels of reduced NAD (NADH), reduced NADP (NADPH), and GSH is as harmful as oxidative stress and is implicated in many pathological processes. Reductive stress broadens our view of the importance of cellular redox homeostasis and the influences of an imbalanced redox niche on biological functions, including cell metabolism. The distribution of cellular NAD(H), NADP(H), and GSH/GSH disulfide is highly compartmentalized. Understanding how cells coordinate different pools of redox couples under unstressed and stressed conditions is critical for a comprehensive view of redox homeostasis and stress. It is also critical to explore the underlying mechanisms of reductive stress and its biological consequences, including effects on energy metabolism. Future studies are needed to investigate how reductive stress affects cell metabolism and how cells adapt their metabolism to reductive stress. Whether or not NADH shuttles and mitochondrial nicotinamide nucleotide transhydrogenase enzyme can regulate hypoxia-induced reductive stress is also a worthy pursuit. Developing strategies ( , antireductant approaches) to counteract reductive stress and its related adverse biological consequences also requires extensive future efforts.